Investigando a ecologia trófica de planárias terrestres neotropicais : ecomorfologia, desenvolvimento e comportamento - Boll, Piter Kehoma (Universidade do Vale do Rio dos Sinos, 2019)
The role of predators in structuring communities is well studied in groups such as vertebrates and spiders, while the role of other admittedly important predators, such as land planarians, is little known. Land planarians for a diverse group of terrestrial flatworms, especially in tropical regions, and are carnivorous, mostly predators, but their sensitivity to environmental changes makes them difficult to keep in the laboratory, which reduces the number of studies on their behavior. For example, the feeding habits of most species, including the composition of their diet and their predatory behavior, is unknown. Due to the relevance of studies on the trophic ecology of land planarians for the adequate management of their populations, this work aimed to enrich the knowledge on the morphological, physiological and behavioral diversity of land planarians regarding their diet and their predatory behavior. To facilitate the identification of food items without the need to conduct exhaustive offers of possible prey, we compared morphological variables of several planarian species to their known feeding habits. The results indicate that the thickness of the cutaneous musculature is a more important variable to define the diet of land planarians than pharynx anatomy, suggesting a higher diversity in the morphological adaptation for capturing prey and lower for prey consumption. In a species of more generalist habits, which includes both gastropods and other planarians in its diet, we examined the influence of different diets on survival, growth and fecundity. Specimens receiving a mixed diet (planarians + slugs) survived, on average, less than specimens feeding only on planarians or only on slugs. In the mixed group, there was a preference for planarians. There was no significant difference in growth between the groups. The larger number of egg capsules was laid by specimens feeding only on slugs but the group receiving the mixed diet laid heavier capsules. The constant alternation between different food items seems to have negative effects on the planarians, suggesting the need for great physiological changes to digest different prey items. The heavier capsules laid by the group that had the lowest survival suggest terminal investment, with an increase in reproductive investment at the end of life. Finally, we examined the behavior of prey detection and the behavior of predator recognition in a land planarian that feeds on woodlice and is the prey of other land planarians. The planarian was unable to detect remote chemical and mechanical signals of the prey and did not follow chemical trails of the prey, suggesting an ambush behavior for prey capture. When touched directly by a predator, the planarian showed an immediate escape response, which did not occur when touched by non-predators. Species phylogenetically close to predators, but which are not themselves predators of the planarians, also triggered an escape response, suggesting similar chemical signatures that cannot be distinguished by the planarian. Chemical secretions and trails alone rarely triggered an escape response, indicating the need for tactile stimuli or a subtler avoidance response that was not detected. The ambush behavior for the capture of woodlice and the quick escape response in the presence of a predator planarian seem adequate strategies for the capture of fast-moving prey and the escape from slow-moving predators. In overall, the results highlight the great morphological, ecological and behavioral diversity of land planarians.
Keywords: Comportamento; Ecomorfologia; Geoplanidae; Hábitos alimentares; Behavior; Ecomorphology; Feeding habits; Geoplanidae; ACCNPQ::Ciências Biológicas::Biologia Geral